2017
DOI: 10.1007/s11746-017-3036-5
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Differentiation of Greek Extra Virgin Olive Oil from Late‐Harvested Koroneiki Cultivar Fruits

Abstract: Seventy‐four monovarietal olive oil samples belonging to the Koroneiki cultivar were collected from four selected olive oil‐producing regions of Greece (Messinia, Lakonia, Irakleio and Etoloakarnania), during two harvesting periods (2012/2013 and 2013/2014) at the stage of full maturation (maturation index 5–6). Determination of volatile compounds (VC), fatty acid (FA) composition, total phenolic content (TPC) and color parameters was carried out in an effort to classify Koroneiki olive oil samples according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…During storage, hexanal, initially present in fresh oil, can be depleted as well, but further, hexanal can be produced from secondary oxidation from hydroperoxydes . Most of the studies, when indicated, measured volatile compounds few days after the production directly or after storage between 4 and −20°C until analysis . Our samples were measured after 3 months of storage, protected from the light, at 12°C that is the typical time occurring between production and commercialisation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During storage, hexanal, initially present in fresh oil, can be depleted as well, but further, hexanal can be produced from secondary oxidation from hydroperoxydes . Most of the studies, when indicated, measured volatile compounds few days after the production directly or after storage between 4 and −20°C until analysis . Our samples were measured after 3 months of storage, protected from the light, at 12°C that is the typical time occurring between production and commercialisation.…”
Section: Resultsmentioning
confidence: 99%
“…20 Most of the studies, when indicated, measured volatile compounds few days after the production directly or after storage between 4 and −20°C until analysis. 16,19,[21][22][23][24][25] Our samples were measured after 3 months of storage, protected from the light, at 12°C that is the typical time occurring between production and commercialisation. Hexanal has been reported to be negatively correlated with leaf and lawn attributes other than to flower and tomato attributes while was positively correlated to almond attribute and, in combination with (Z)-3-hexenyl acetate, to banana odour.…”
Section: Quantification Of Volatile Compounds In Oilsmentioning
confidence: 99%
“…Thus, for samples produced in Crete the concentration of 18:1 has been reported to be in the range 71.6-79.9%, that of 16:0 from 10.4 to 13% and of 18:2 within 5.0 to 9.8% (n ¼ 53, [38] n ¼ 4, [39] n ¼ 3, [40] n ¼ 16 [41] ). These were 0.1, below the legal limit ( 0.2).…”
Section: Fatty Acids and Triacylglycerol Compositionmentioning
confidence: 97%
“…These were 0.1, below the legal limit ( 0.2). The content of 18:1, 16:0, and 18:2 of VOOs from cv Koroneiki deriving from Peloponnese, mostly from Messinia, ranged from 66.8 to 78.3, 9.77 to 19.4, and 5.6 to 8.8%, respectively (n ¼ 49 [41] , n ¼ 32, [42] n ¼ 12, [43] n ¼ 8, [44] n ¼ 40 [45] ). Nevertheless, limited were also the measurements for trilinolein content since only for "Messara" and "Peza Irakliou Kritis" the corresponding levels have been determined (0.11 and 0.136, respectively).…”
Section: Fatty Acids and Triacylglycerol Compositionmentioning
confidence: 99%
See 1 more Smart Citation